2002
DOI: 10.1021/jm010458r
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Cyclooxygenase-2 Selective Inhibitors Using Pharmacophore Models

Abstract: In the present study we have investigated whether pharmacophore models may account for the activity and selectivity of the known cyclooxygenase-2 (COX-2) selective inhibitors of the phenylsulfonyl tricyclic series, i.e., Celecoxib (1) and Rofecoxib (3), and whether transferring this structural information onto the frame of a nonsteroidal antiinflammatory drug (NSAID), known to tightly bind the enzyme active site, may be useful for designing novel COX-2 selective inhibitors. With this aim we have developed a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 29 publications
4
118
0
1
Order By: Relevance
“…Thus, the common features of all the generated hypotheses were summarized and used as the query features in the virtual screening. In addition, the excluded volumes were involved in the pharmacophore models to improve effectiveness of virtual screening [42][43][44] . All the pharmacophore models were exported and translated by a script into Catalyst pharmacophore files for further virtual screening.…”
Section: Pharmacophore Model Generationmentioning
confidence: 99%
“…Thus, the common features of all the generated hypotheses were summarized and used as the query features in the virtual screening. In addition, the excluded volumes were involved in the pharmacophore models to improve effectiveness of virtual screening [42][43][44] . All the pharmacophore models were exported and translated by a script into Catalyst pharmacophore files for further virtual screening.…”
Section: Pharmacophore Model Generationmentioning
confidence: 99%
“…2-( 4-Substituted-phenyl ) -5-( naphthalen-1-yloxymethyl)- [1,3,4]oxadiazole (5a f): A mixture of 4a f (0.01 mol), anhydrous sodium acetate (0.02 mol), and glacial acetic acid was placed in a round-bottomed ‰ask equipped with a separating funnel for the addition of bromine. Bromine (0.8 ml in 5 ml of glacial acetic acid) was added slowly to it while stirring magnetically.…”
Section: Chemistrymentioning
confidence: 99%
“…1,3,4-Oxadiazoles have antiin‰ammatory properties by virtue of a dual mechanism, i.e., inhibiting both COX and LOs to reduce gastric ulcer formation. 1,2) Numerous studies have been performed with the aim of exploring the antiin‰ammatory properties of 1,3,4-oxadiazole analogues. 3 7) Those studies found that 1,3,4-oxadiazole analogues are equipotent with phenylbutazone, naproxen and other NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…Although both isoforms catalyze the same biochemical transformation, they are subject to a different expression regulation. COX-1 is a constitutive enzyme and is responsible for the physiological function of prostaglandins (PGs) like maintenance of the integrity of the gastric mucosa and provides adequate vascular homeostasis, whereas COX-2 is an inducible enzyme and is expressed only after an inflammatory stimulus [1]. In recent years, many heterocyclic moieties have been designed and synthesised as potent antiinflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%